Variation of 137Cs and 239, 240Pu Concentrations in Shellfishes on the Coast of Ibaraki Prefecture - FUJITA, Hiroki; NAKANO, Masanao (Hoken butsuri, 2007)
The concentrations of 137Cs and 239, 240Pu in shellfishes collected from the coast around the Tokai Reprocessing Plant (TRP) from 1975 to 2005 were analyzed for environmental radiological monitoring. The measured concentrations of 238Pu were under the detection limits and these concentrations of 137Cs and 239, 240Pu showed no significant short-term increase tendency. It was confirmed that 137Cs and 239, 240Pu in shellfishes around the TRP were derived from the past atmospheric nuclear weapons tests. Also the probability plot of 239, 240Pu concentration was dependent on the shellfish species (bivalve and abalone). It was presumed that the difference of feeding behavior of bivalve and abalone caused the difference of the probability plot of 239, 240Pu concentration.